Comparative anaerobic digestion of sewage sludge at different temperatures with and without heat pre-treatment. (November 2022) - Hidaka, Taira; Nakamura, Masato; Oritate, Fumiko; Nishimura, Fumitake
Abstract: Anaerobic digestion of sewage sludge is generally conducted under mesophilic (around 35 °C) or thermophilic (around 55 °C) conditions, whereas it is conducted at lower temperatures in some wastewater treatment plants without heating. In this study, we compared the anaerobic digestion of sewage sludge at 15, 25, 30, 35, 45, and 55 °C following hyperthermophilic pre-treatment at 80 °C for 24 h. Laboratory-scale reactors were operated continuously for more than 1000 days, and batch experiments were performed to evaluate the reaction kinetics. Biogas production rates at 15 °C with and without pre-treatment divided by that at 35 °C without pre-treatment were 0.73 and 0.78, respectively. The dewaterability of the digested sludge was evaluated by the capillary suction time (CST). The CST was approximately 50 s at 15 °C with and without pre-treatment and was slower than the CST at 35 °C. Compared to the shear rate, viscosity was higher at lower temperatures; however, it decreased with pre-treatment, which reduced the energy required for mixing in the reactors. Pre-treatment eliminated Escherichia coli from the sludge; however, E. coli (approximately 10 5 colony forming unit/g-total solids) was detected after digestion at temperatures ≤30 °C. Pre-treatment was also useful to replace a part of heat treatment required for digested sludge before it was used as fertilizer. Gene sequencing analyses indicated the effects of pre-treatment and digestion temperature on the microbial community in the digested sludge. Co-generation of biogas is useful to obtain both electricity and heat; however, heat from co-generation is sometimes limited. To maximize electricity recovery, the use of low temperature digesters has the potential to reduce fuel costs. The results indicate that anaerobic digestion at low temperatures with or without heat pre-treatment can be an efficient and cost-effective method of treating sewage sludge. Graphical abstract: Image 1 Highlights: Anaerobic digestion at low temperatures is cost-effective and consume less energy. Hyperthermophilic pre-treatment enhances biodegradation speed. Hyperthermophilic pre-treatment reduces viscosity and required energy for mixing. Hyperthermophilic pre-treatment is beneficial for fertilizer utilization. A combination of lower temperatures and hyperthermophilic pre-treatment is promising.